THE CONCEPT OF ISLAMIC EDUCATION IN THE PERSPECTIVE OF SHEIKH BURHAN Al-DIN Al-ZARNUJI AND ITS RELEVANCE FOR EDUCATION IN INDONESIA - Nasrodin Nasrodin; Moch. Tohet; Firma Yudha (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to find out the thoughts of Sheikh al-Zarnuji in the book Ta'lim Muta'allim and its relevance for education in Indonesia. It is based on education not only limited to the transfer of knowledge, but rather the application of spiritual, religious and ethical values. This research uses library research because researchers only study and read literature that has something to do with the problem of the object of research. Data sources in the form of Kitab Ta‟lim Al-Muta‟llim, and supporting books, data obtained through documentation and observation, data analysis techniques using content analysis, Inductive, and constitutional methods, while validity techniques use research dependence on the data obtained. The results show that 1) In ethics, al-Zarnuji emphasizes more on the ethics of students than educators. 2) Of the thirteen chapters in Kitab Ta'lim Al-Muta'llim, they are classified into four points including the understanding and purpose of science, intention, learning methods, surrender (Tawakkal). 3) The relevance of al-Zarnuji's educational thought in the book of Ta'lim Muta'allim to current educational thinking, especially in Indonesia, is seen in aspects: educational objectives, educators, students, curriculum, and educational methods.